Implementation of Physics Learning Media Using Kakula Musical Instruments on Student Learning Outcomes on Sound Wave Materials - Wanda Wanasita; Rudi Santoso; Unggul Wahyono; Ketut Alit Adi Untara (Jurnal Ilmiah Pendidikan Fisika, 2025)
Physics education at the high school level still faces challenges in improving student learning outcomes on abstract concepts such as sound waves. Many instructional approaches lack contextual or culturally relevant elements that can make learning more engaging and meaningful. This research explores the integration of local cultural elements into physics education using the Kakula musical instrument as a contextual learning tool. Using a quasi-experimental method guided by the Educational Reconstruction model, this study examines the academic validity of the learning media and its impact on student learning outcomes. The kakula instrument, rich in acoustic properties, was used to teach the concepts of waves and sounds within a problem-based learning framework. The experiment showed a statistically significant improvement in learning outcomes, with average post-test scores increasing from 59.94 to 70.53. Statistical tests, including normality, homogeneity (Bonett and Levene), and a t-test, showed a p-value of 0.0001 < 0.05, which means that the null hypothesis is rejected. The alternative hypothesis is accepted, indicating a significant effect of physics learning media using the Kakula musical instrument on student learning outcomes on the topic of sound waves. The results of the research can serve as a basis for developing culturally integrated teaching materials while preserving local heritage and enriching science education practices.